Classification of field dwarfs and giants in RAVE and its use in stellar stream detection - Klement, Rainer J.; Bailer-Jones, Coryn A. L.; Fuchs, Burkhard; Rix, Hans-Walter; Smith, K. W. (The astrophysical journal, 2011)
Samples of bright stars, as they emerge from surveys such as RAVE, contain comparable fractions of dwarf and giant stars. An efficient separation of these two luminosity classes is therefore important, especially for studies in which distances are estimated through photometric parallax relations. We use the available spectroscopic log g estimates from the second RAVE data release (DR2) to assign each star a probability for being a dwarf or subgiant/giant based on mixture model fits to the log g distribution in different color bins. We further attempt to use these stars as a labeled training set in order to classify stars which lack log g estimates into dwarfs and giants with a Support Vector Machine algorithm. We assess the performance of this classification against different choices of the input feature vector. In particular, we use different combinations of reduced proper motions, 2MASS JHK, DENIS IJK, and USNO-B B2R2 apparent magnitudes. Our study shows that - for our color ranges - the infrared bands alone provide no relevant information to separate dwarfs and giants. Even when optical bands and reduced proper motions are added, the fraction of true giants classified as dwarfs (the contamination) remains above 20%. Using only the dwarfs with available spectroscopic log g and distance estimates (the latter from Breddels et al.), we then repeat the stream search by Klementet al. (KFR08), which assumed that all stars were dwarfs and claimed the discovery of a new stellar stream at V ≈ −160 km s−1 in a sample of 7015 stars from RAVE DR1. The existence of the KFR08 stream has been supported by two recent studies using other independent data sets. Our re-analysis of the pure DR2 dwarf sample exhibits an overdensity of five stars at the phase-space position of the KFR08 stream, with a metallicity distribution that appears inconsistent with that of stars at comparably low rotational velocities. Compared to several smooth Milky Way models, the mean standardized deviation of the KFR08 stream is only marginal at 1.6 ± 0.4. Our data therefore do not allow to draw definite conclusions about its existence, but future RAVE data releases and other (best spectroscopic) surveys are going to help in resolving this issue.
Published 2010 December 21
Gesehen am 18.08.2022